Successful Outcome of a Corticodependent Henoch-Schönlein Purpura Adult with Rituximab - Taylor Pindi Sala; Jean-Marie Michot; Renaud Snanoudj; Marion Dollat; Emmanuel Estève; Bernadette Marie; Yacine Taoufik; Jean-François Delfraissy; Thierry Lazure; Olivier Lambotte (Case Reports in Medicine)
Henoch-Schönlein purpura (HSP) is a systemic vasculitis involving small vessels with deposition of immunoglobulin A (IgA) complexes, usually affecting children. Compared with children, HSP in adults is more severe and frequently associated with cancer. We report the case of a 49-year-old woman with medical history of kidney transplantation for segmental glomerular hyalinosis. Eight years after the transplantation, while taking combined immunosuppressive therapy with tacrolimus and azathioprine indicated for the prevention against transplant rejection, she developed a Henoch-Schönlein purpura. Vasculitis involves skin and sciatic peroneal nerve and she received systemic corticosteroid treatment. Because of four relapses and corticosteroid dependence, the patient was treated with rituximab (two intravenous infusions of 1000 mg given two weeks apart). Successful outcome was observed along two years of follow-up. This new case of successful use of rituximab in HSP promotes more investigations of this treatment in clinical trials.